Quantitative nuclear cardiology and assessment of areas under risk via adenosine stress protocol-A pictorial assay for cardiologists and cardiovascular surgeons during era of COVID - Nese İlgin Karabacak; Edanur Tuncay Ibıs; Salih Demir; Merve Uluç Balım; Bariş Kücükali; Rıdvan Yalcın (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2022)
Coronary Artery Disease (CAD) is one of the most important causes of mortality and morbidity in the world. Nevertheless, Myocardial Perfusion Scintigraphy (MPS) using Single-Photon Emission Computed Tomography (SPECT) with radiopharmaceuticals is still widely used for the non-invasive diagnosis of obstructive CAD and functional imaging of the myocardium at stress. MPS provides comprehensi